APKASS Consensus Statement on Chronic Syndesmosis Injury, Part 3: Fusion Techniques, Comorbidity Treatments, Postoperative Rehabilitation, and Return-to-Sport Indications - Yujie Song; Zhongmin Shi; Hiroaki Kurokawa; Yasuhito Tanaka; Samuel Ka-Kin Ling; Patrick Shu‐Hang Yung; Chayanin Angthong; Seung Hwan Han; Yinghui Hua; Hongyun Li; Chen Jiao; Jianchao Gui; et al. (Orthopaedic Journal of Sports Medicine, 2021)
BACKGROUND: Questions regarding surgical fusion techniques, postoperative treatment, and indications for return to sport after chronic syndesmosis injury or its comorbidities remain unanswered. PURPOSE: An international group of experts representing the field of injuries in the foot and ankle area was invited to collaboratively advance toward consensus opinions based on the best available evidence regarding chronic syndesmosis injury. All were members of the Asia-Pacific Knee, Arthroscopy and Sports Medicine Society (APKASS). STUDY DESIGN: Consensus statement. METHODS: From November to December 2020, a total of 111 international experts on sports medicine or ankle surgery participated in a 2-stage Delphi process that included an anonymous online survey and an online meeting. A total of 13 items with 38 statements were drafted by 13 core authors. Of these, 4 items with 6 clinical questions and statements were related to surgical fusion techniques, comorbidity treatments, postoperative rehabilitation, and return-to-sports indications and are presented here. Each statement was individually presented and discussed, followed by a general vote. The strength of consensus was characterized as follows: consensus, 51% to 74%; strong consensus, 75% to 99%; and unanimous, 100%. RESULTS: Of the 6 questions and statements, 5 achieved unanimous support and 1 reached strong consensus. CONCLUSION: This APKASS consensus statement, developed by international experts in the field, will assist surgeons and physical therapists with surgical and postoperative treatment strategies for chronic syndesmosis injury.
Keywords: Foot and Ankle Surgery; Knee injuries and reconstruction techniques; Lower Extremity Biomechanics and Pathologies